2018
DOI: 10.1002/pen.24891
|View full text |Cite
|
Sign up to set email alerts
|

Effects of organic acids on the performance of cellulose triacetate forward osmosis membrane

Abstract: Forward osmosis (FO) membrane performance was improved using different organic acids (formic acid, acetic acid, lactic acid) for the addition of the casting solution. Scanning electron microscope (SEM) images of all the FO CTA membranes exhibited essentially the membranes have a structure of looking like two dense skin layers and a sponge‐like supporting layer. Additionally, based on the surface roughness values analysis of Atomic Force Microscope (AFM), the membranes with lactic acid, with similar roughness t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Several attempts have been made to improve the performance of FO membranes either by increasing the flux or reducing the reverse solute flux via membrane modification or composition optimization methods. 28,29 The fouling on the membrane is an inevitable phenomenon that needs to be checked 30 and removed regularly to improve the life of the membrane. Numerous research studies have been demonstrated to improve the antifouling property of membranes via surface modification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several attempts have been made to improve the performance of FO membranes either by increasing the flux or reducing the reverse solute flux via membrane modification or composition optimization methods. 28,29 The fouling on the membrane is an inevitable phenomenon that needs to be checked 30 and removed regularly to improve the life of the membrane. Numerous research studies have been demonstrated to improve the antifouling property of membranes via surface modification.…”
Section: Introductionmentioning
confidence: 99%
“…Fouling is a significant issue in the membrane that hinders the membrane performance, membrane life, and water flux efficiency. Several attempts have been made to improve the performance of FO membranes either by increasing the flux or reducing the reverse solute flux via membrane modification or composition optimization methods 28,29 . The fouling on the membrane is an inevitable phenomenon that needs to be checked 30 and removed regularly to improve the life of the membrane.…”
Section: Introductionmentioning
confidence: 99%
“…CA membranes are produced from the acetylation of cellulose to obtain cellulose triacetate (CTA) and cellulose diacetate acetate by acetic anhydride. [ 10‐15 ] Cellulose is a natural product, asymmetric polymer (crystalline and amorphous). It could extract from natural products of agricultural like fiber.…”
Section: Introductionmentioning
confidence: 99%